Construction of novel g-C3N4 coupled efficient Bi2O3 nanoparticles for improved Z-scheme photocatalytic removal of environmental wastewater contaminant: Insight mechanism. (15th March 2023) - Ranjith, R.; Vignesh, S.; Balachandar, Ramalingam; Suganthi, S.; Raj, V.; Ramasundaram, Subramaniyan; Kalyana Sundar, J.; Shkir, Mohd; Oh, Tae Hwan
Abstract: Recently, the major environmental pollution produced by the release of wastewater in liquid type is one of the most extensive forms of foremost pollution in water ecosystems. In this article, the Bi2 O3 /g-C3 N4 nanocomposite with a direct Z-scheme was effectively obtained by a facile hydrothermal system. The crystal structures, surface morphology, chemical composition, and the optical belongings of the as-obtained composite catalysts were examined by Power XRD, FT-IR spectra, High-resolution XPS spectra, FE-SEM images with EDX spectra, High-resolution TEM images, UV–Vis DRS, and PL spectra respectively. Furthermore, the photocatalytic performance was assessed by the degradation of aqueous Rhodamine B (Rh B) dye under visible-light exposure. The Bi2 O3 /g-C3 N4 composite photocatalysts (PCs) showed the maximum photo-degradation efficiency through a rate constant value of 0.0149 min −1, which is 4.9 and 5.3 folds superior to Bi2 O3, and GCN, respectively. The better GBO2 nanocomposite PCs showed a superior photocatalytic degradation performance (>82%) of aqueous Rh B dye after five successive recycles. Moreover, based on these outcomes of the radical scavenging test, a direct and effective Z-scheme photocatalytic charger transfer mechanism was also projected. Finally, the reusability of the as-obtained Bi2 O3 /g-C3 N4 nanocomposite has better stability and reusability, which was a favourable applicant for wastewater handling. Highlights: Bi2O3/g-C3N4 composite Z-scheme catalyst was effectively obtained by facile way. The superior photocatalytic Rh B dye degradation activity (88.5%) under light exposure. Reaction rate constant of GBO2 catalyst (0.0149 min-1) is 4.9 folds superior to Bi2O3. Better recycling stability and durability of Rh B dye after five successive recycles. Also, an effective Z-scheme photocatalytic charger transfer mechanism was proposed.